Fetal Diagnosis of Left Ventricular Aneurysm: A Case Report - Giacobbe, Lauren; Williams, Preston; Ramin, Kirk; Sivanandam, Shanthi (American Journal of Perinatology Reports, 2011)
Congenital left ventricular aneurysm is a rare but potentially lethal condition. We describe a case of isolated congenital left ventricular aneurysm diagnosed at 28 weeks' gestation. In addition to standard imaging, we utilized color-coded transthoracic tissue Doppler techniques to further evaluate the aneurysm postnatally.
Keywords: Fetal echocardiography; ventricular aneurysm; congenital heart disease; ultrasound